Trends of Problem-Solving Skills Research in Journal of Mathematics Education in Indonesia - Shafa Salsabila; Endang Cahya Mulyaning A; Tiara Aurelly Ferta (Departemen Pendidikan Matematika, FPMIPA, UPI, 2024)
This study aims to analyze articles published in Indonesian mathematics education journals to see the development of problem-solving skills research. Content analysis is the method used to analyze these articles. The articles analyzed were articles published in 2019 to 2024, with a special emphasis on problem-solving skills. After being analyzed, it was found that there was a decrease in the number of publications discussing problem-solving skills over the past five years. Of these articles, the most commonly used research design was quantitative. In addition, the eighth grade of junior high school and the material 'Geometry' were consistently the most widely used subjects and materials in this study. Test sheets and t-tests were the instruments and data analysis methods most widely used by researchers. Several suggestions have been put forward for future problem-solving skills research. One of the main suggestions is to increase the variety of research methodologies used. Researchers are encouraged to not only rely on quantitative methods, but also explore qualitative and mixed methods to gain a deeper understanding of how problem-solving skills can be developed effectively. More diverse research in terms of subjects, topics, and methodologies is expected to make a significant contribution to improving the quality of mathematics education in Indonesia, especially in developing students' problem-solving skills.